Tourism demand and corruption: Are the impacts of relative corruption on international tourist arrivals in Thailand relevant? - Chulaphan, Wanvilai; Barahona Caceres, Jorge (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2021)
This article evaluates the impact of relative corruption on international tourist arrivals in Thailand using a generalized least squares estimator. We compile a panel dataset that consists of data from 29 countries from 2010 to 2017. The results suggest that relative corruption has a detrimental impact on international tourist arrivals. Moreover, the effect of relative corruption is greater as the distance of corruption between Thailand and the country of origin increases. As a consequence, tourist authorities should develop specific marketing strategies based on the relative levels of corruption exhibited in the tourist market. Furthermore, governments should build long-term and short-term tourism policies that aim at improving tourist perception of corruption in Thailand.